The Effects of Intraperitoneal and Subcutaneous Insulin Application on Peritoneal Solute Permeability and Ultrafiltration in Experimental Model of Diabetes - Özalp, Göksel; Işık, Ahmet (Fırat University, 2007)
Objectives: Ultrafiltration (UF) insufficiency is one of the important causes of inadequate dialysis. Intraperitoneal (IP) insulin might be administered for blood glucose regulation in diabetic peritoneal dialysis patients. Insulin is known to increase the development of fibrosis and neovascularization via increasing growth factors like TGF-β1 and VEGF. In our study, we aimed to investigate the effects of IP and subcutaneous (SC) insulin application on the peritoneal membrane permeability. Material and Methods: 24 wistar albino rats were included in the study and three groups were formed. The first group was the control one. IP insulin for the 2nd group and SC insulin for the 3rd group rats in which diabetes was induced by 60 mg/kg streptozocin were applied. 2 mounts later all the rats underwent peritoneal equilibration test and quantification of UF. Results: When compared with the control group UF quantity decreased in two diabetic groups and the decrease in the IP insulin group was significant (p

Giriş: Ultrafiltrasyon (UF) yetersizliği, periton diyalizi hastalarında en önemli diyaliz yetersizliği nedenlerinden birisidir. Diyabetik periton diyalizi hastalarında kan şekeri regülasyonu için intraperitoneal (İP) insülin uygulanabilmektedir. İnsülinin, TGF-β1 ve VEGF gibi büyüme faktörlerini artırarak fibroz gelişimi ve yeni damar oluşumlarına neden olduğu bilinmektedir. Çalışmamızda, deneysel diyabet modelinde, İP ve subkutan (SC) insülin uygulamalarının peritoneal membran geçirgenliği üzerine etkilerinin incelenmesi amaçlandı. Gereç ve Yöntem: Çalışmaya, 24 adet wistar albino türü sıçan alındı. Sıçanlar üç gruba ayrıldı. 1. grup kontrol grubu olarak kullanıldı. 60 mg/kg dozunda İP streptozosin uygulanarak diyabetik hale getirilen sıçanlardan 2. gruba İP, 3. gruba ise SC insülin uygulandı. 2 ay sonra tüm sıçanlara, peritoneal eşitlenme testi yapıldı ve UF miktarları hesaplandı. Bulgular: Heriki diyabetik grupta, kontrol grubuyla karşılaştırıldığında, UF miktarlarında azalma vardı ve İP insülin grubundaki azalma anlamlıydı (p
Deneysel Diyabet Modelinde İntraperitoneal ve Subkutan İnsülin Uygulanmasının Peritoneal Solüt Geçirgenliği ve Ultrafiltrasyon Üzerine Etkileri